THE CONTRIBUTION OF TRADITIONAL GAMES IN ESTABLISHING SELF-CONTROL CHILDREN - Bernadeta Tri Anjarwati Kusuma Wardani; Gregorius Ari Nugrahanta (Nurul Jadid University, 2021)
This research intended to develop a traditional game guidebook to improve self-control for children aged 9-12. This research method was R&D. Research conducted involved seven validators for expert judgment, seven teachers who were certified educators for needs analysis, and six children through subjects of a limited trial of the developed traditional game guidebook. The results indicated that; 1) development of this traditional game guidebook using ADDIE, 2) traditional game guidebook belonging to the